2021
DOI: 10.1016/j.molcel.2021.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase 1 activity during mitotic transcription favors the transition from mitosis to G1

Abstract: Highlights d TOP1 promotes RNAPII transcription and clearance from chromosomes in prometaphase d TOP1 assists RNAPII promoter loading during mitotic exit to restart transcription d Loss of TOP1-RNAPII interaction causes supercoil buildup and segregation defects d Disrupting TOP1-RNAPII binding affects growth and sensitizes cells to mTOR drugs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 96 publications
(137 reference statements)
0
14
0
Order By: Relevance
“…Chromatin immunoprecipitation of GapR combined with high-throughput sequencing was used to generate maps of positive supercoiling in bacteria and yeast [ 97 ]. Detection of topoisomerase activity sites (Middle panel) and non-B DNA structures (Bottom panel) are also powerful methods to predict DNA supercoiling in vivo [ 71 , 132 , 146 ]. There has been considerable concordance between the studies supporting the main prophecies of the twin-supercoiled domain model: negative torsional stress accumulated at the upstream promoter region of the active genes, while positive torsional stress accrues in a transcription-dependent manner in gene bodies and downstream to the 3’ ends of genes.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromatin immunoprecipitation of GapR combined with high-throughput sequencing was used to generate maps of positive supercoiling in bacteria and yeast [ 97 ]. Detection of topoisomerase activity sites (Middle panel) and non-B DNA structures (Bottom panel) are also powerful methods to predict DNA supercoiling in vivo [ 71 , 132 , 146 ]. There has been considerable concordance between the studies supporting the main prophecies of the twin-supercoiled domain model: negative torsional stress accumulated at the upstream promoter region of the active genes, while positive torsional stress accrues in a transcription-dependent manner in gene bodies and downstream to the 3’ ends of genes.…”
Section: Overviewmentioning
confidence: 99%
“…If the genomic distribution of positive supercoiling is disturbed, the next cell cycle is impaired. The study shows that during mitotic transcription [ 131 ], Pol II and Top1 coordinate their activities [ 132 ]. Deregulated Pol II-Top1 coordination or acute degradation of Top1 cause mitotic defects, cell cycle delays, and impaired transcription in the following cell cycle.…”
Section: Mechanical Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear membrane also loses its continuity in mitotic cells and no longer serves as a tight barrier between the cytoplasm and chromatin (3). Given that transcription is rapidly re-established after cell division (2, 4), mechanisms must exist to facilitate the precise and accurate reestablishment of gene expression after mitosis (5). One proposed mechanism, termed mitotic bookmarking, suggests that the binding of proteins, mainly transcription factors (TFs), to specific genomic loci during mitosis marks genes for rapid activation after cell division (6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human cells proposed that the transcription termination Factor 2 (TTF2) drives the removal of active PolII in mitosis (Liu et al , 1998) whereas the transcription initiation inhibitor Gdown1 was shown to gain access to chromatin solely during mitosis to repress mitotic transcription (Ball et al , 2022). Recent studies have also proposed that specific mechanisms ensure promoter clearance upon mitotic entry, mediated by PolII-mediated activation of Top1, to release topological stress (Wiegard et al , 2021) or hyperactivation of P-TEFb, to enhance transcriptional elongation (Liang et al , 2015).…”
Section: Introductionmentioning
confidence: 99%